Coprophilic amoebae and flagellates, including Guttulinopsis, Rosculus and Helkesimastix, characterise a divergent and diverse rhizarian radiation and contribute to a large diversity of faecal‐associated protists. (7th April 2016) - Bass, David; Silberman, Jeffrey D.; Brown, Matthew W.; Pearce, Rebecca A.; Tice, Alexander K.; Jousset, Alexandre; Geisen, Stefan; Hartikainen, Hanna
Summary: A wide diversity of organisms utilize faecal habitats as a rich nutrient source or a mechanism to traverse through animal hosts. We sequenced the 18S rRNA genes of the coprophilic, fruiting body‐forming amoeba Guttulinopsis vulgaris and its non‐fruiting relatives Rosculus 'ithacus' CCAP 1571/3, R. terrestris n. sp. and R. elongata n. sp. and demonstrate that they are related to the coprophilic flagellate Helkesimastix in a strongly supported, but highly divergent 18S sister clade. PCR primers specific to both clades were used to generate 18S amplicons from a range of environmental and faecal DNA samples. Phylogenetic analysis of the cloned sequences demonstrated a high diversity of uncharacterised sequence types within this clade, likely representing previously described members of the genera Guttulinopsis, Rosculus and Helkesimastix, as well as so‐far unobserved organisms. Further, an Illumina MiSeq sequenced set of 18S V4‐region amplicons generated from faecal DNAs using universal eukaryote primers showed that core‐cercozoan assemblages in faecal samples are as diverse as those found in more conventionally examined habitats. These results reveal many novel lineages, some of which appear to occur preferentially in faecal material, in particular cercomonads and glissomonads. More broadly, we show that faecal habitats are likely untapped reservoirs of microbial eukaryotic diversity.